Tele-psychotherapy during the COVID-19 pandemic: a mini-review - Nicolas Tajan; Maud Devès; Maud Devès; Rémy Potier (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic has dramatically changed psychotherapy practices. Psychotherapy around the world has shifted from predominantly face-to-face settings to overwhelmingly online settings since the beginning of the pandemic. Many studies have been published on this topic, but there has been no review of the literature focused on the experience of psychotherapists. Our goal was to identify the challenging issues of teletherapy, including the efficiency of online consultations and the extent to which they are accepted by therapists and patients. A PubMed literature search using the [(“Teletherapy” OR “Telebehavioral health” OR “telepsychotherapy”) AND (“COVID-19”)] search string retrieved 46 studies focused on mental health professionals, as detailed in a PRISMA flow diagram. Two reviewers independently screened the abstracts and excluded those that were outside the scope of the review. The selection of articles kept for review was discussed by all three authors. Overall, the review contributes to the description and evaluation of tele mental health services, including teletherapy, online counseling, digital mental health tools, and remote monitoring.